ОСОБЛИВОСТІ НАВЧАННЯ МАЙБУТНІХ УЧИТЕЛІВ ІНФОРМАТИКИ РОБОТІ ІЗ СИСТЕМОЮ КОНТРОЛЮ ВЕРСІЙ GIT - Mosiiuk , Oleksandr (Науковий вісник Ужгородського університету. Серія: «Педагогіка. Соціальна робота», 2025)
Робота у команді вважається чи не найважливішою навичкою сучасного фахівця, а тим більше педагога. Безперечним є і той факт, що починати розвивати її необхідно ще у школі, зокрема і на уроках інформатики. Тому майбутній вчитель інформатики має знати СКВ та застосовувати їх для організації спільної роботи учнів як на заняттях так і у процесі підготовки учнівських робіт для МАН. У той же час ця тематика не є достатньо розробленою, а отже вибрана тема статті є актуальною, а її мета полягає в розкритті основних питань навчання роботи студентів із системами контролю версій. Під час дослідження використовувалися такі методи як: аналіз науково-методичних джерел; опис і порівняння результатів; узагальнення. Загалом у статті аналізується особливості навчання майбутніх учителів інформатики роботі з Git і наголошується на важливості засвоєння педагогами відповідного програмного забезпечення. Звертається увага на важливих моментах вивчення команд Git та терміналу Linux для коментування; зауважується на можливостях застосування такого онлайн сервісу як GitHub Classroom. Teamwork is the most important soft skill of the modern specialist, not to mention a teacher. It is also undisputed that skills development is very important to start at school, in particular at computer science lessons. Accordingly, a future teacher of computer science has to know version control systems and use one of them to organize collective student's work like in class and in the process of preparing for science competitions of the Junior Academy of Sciences of Ukraine. This topic of the article is relevant because it doesn't fully describe in the scientific and methodological resources. The main goal of this article is to open the main features of teaching students to work with version control systems on the example of Git. The systematic approach was the methodological basis for the investigation discovery. But besides, the researcher analyzed, compared, and summarized the investigation and experience of the leading scientists. As the result of the article the author rise to the following conclusions that the knowledge of version control systems (in particular Git) is an important part of the preparation of computer science teachers; teaching students to work with such programs have to be combined with the study of programming; should be encouraged students to complete labs and case studies using Git; teachers have to demonstrate through examples the correct organization and culture of work with such programs. The writer is also considering using the GitHub Classroom service to organize the educational process subjects such as programming and page making of web pages.